2016
DOI: 10.1104/pp.16.00965
|View full text |Cite
|
Sign up to set email alerts
|

ORM Expression Alters Sphingolipid Homeostasis and Differentially Affects Ceramide Synthase Activities

Abstract: Sphingolipid synthesis is tightly regulated in eukaryotes. This regulation in plants ensures sufficient sphingolipids to support growth while limiting the accumulation of sphingolipid metabolites that induce programmed cell death. Serine palmitoyltransferase (SPT) catalyzes the first step in sphingolipid biosynthesis and is considered the primary sphingolipid homeostatic regulatory point. In this report, Arabidopsis (Arabidopsis thaliana) putative SPT regulatory proteins, orosomucoidlike proteins AtORM1 and At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(69 citation statements)
references
References 54 publications
(91 reference statements)
7
60
2
Order By: Relevance
“…We favor the first mechanism, in which ORM binds to the SPT complex with the ssSPT interaction, based on a recent study by Kimberlin et al (2016). In addition, we observed that the ORMs and ssSPT localize in the ER, which could be the site where they interact (Figure 1; Supplemental Figure 6).…”
Section: Discussionmentioning
confidence: 70%
“…We favor the first mechanism, in which ORM binds to the SPT complex with the ssSPT interaction, based on a recent study by Kimberlin et al (2016). In addition, we observed that the ORMs and ssSPT localize in the ER, which could be the site where they interact (Figure 1; Supplemental Figure 6).…”
Section: Discussionmentioning
confidence: 70%
“…One of the interesting observations made prior to this analysis was the differential activity in the two classes of ceramide synthase resulting from a perturbation to the level of ORMs in the system. Previous studies postulated that this differential activity potentially points to a possible regulatory interaction between ORMs and the ceramide synthases [19].…”
Section: The Effect Of Perturbations On the Generated Modelmentioning
confidence: 97%
“…To predict plausible regulatory schemes capable of reproducing all of the observed responses, we started with a set of 23 schemes that had been postulated in previous works [19,22].…”
Section: Predicting the Regulatory Scheme Of The Sphingolipid Pathwaymentioning
confidence: 99%
See 2 more Smart Citations